Effect of rootstock girth and varieties of aonla (Emblica officinalis) on propagation - Raj, Raj Kumar; Rai, A K; Kumar, Amit; Khajuria, S; Lata, K (Current Horticulture, 2025)
Five aonla (Emblica officinalis L.), varieties and three rootstock thickness were evaluated for various aspects of propagation under hot semi arid ecosystem of western India during 2010-2013. The rootstock girth and aonla varieties significantly affected all propagation aspects, except survival per cent of budding. The increasing thickness of stock increase plant height, maximum plant height was recorded in Chakaiya (15.06m), followed by Anand 2 (15.02m), Francis (14.26m), Goma Aishwarya (13.02m) and minimum in N.A. -7 (12.55) at >1.5 cm girth of stock. The maximum plant spread in East-West was recorded in Goma Aishwarya (12.05m) followed by Franics (11.50m), Anand 2 (11.02m), Chakaiya (10.08m) and minimum in N.A. 7 (10.96m). In case of North-South maximum was noted in Anand 2 (13.50m) followed by Goma Aishwarya (13.05m), Chakaiya (12.06m), Franics (11.86m) and minimum in N.A. 7 (11.16m) . The maximum stock and scion thickness were recorded in Anand 2 (66.08 and 63.05cm), followed by Frances (62.22 and 57.33cm), in Chakaiya (52.13 and 49.08 cm) in Goma Aishwarya (50.04 and 47.11 cm) and the minimum in N.A. 7 (44.25 and 44.25 cm). The rootstock and scion growth were equal in NA-7, this variety has more budding compatibility than other.